Intercultural Communication and Competence in the Process of Internationalisation of Higher Education Institutions (R&E-SOURCE, 2026)
The internationalisation of higher education institutions is traditionally evaluated using quantitative indicators such as student mobility and international partnerships. However, its qualitative dimension—particularly everyday intercultural communication and academic inclusion—remains underexplored. This paper examines intercultural communication as a key determinant of the quality of internationalisation at the University of Žilina (UNIZA). The aim of the study was to identify perceptual differences between university teachers and international students regarding intercultural preparedness, language clarity, participation, and adaptation to the academic environment. A quantitative questionnaire survey conducted among staff members and international students was analysed using descriptive and comparative methods. The findings indicate that an inclusive academic environment does not emerge automatically from diversity itself but requires the systematic development of intercultural competence among university staff and students. Based on the identified needs, a set of developmental activities was implemented, including the creation of a document entitled Ten Principles of Intercultural Communication, the development of a methodological guide, and the organisation of intercultural workshops. The paper highlights the necessity of the systematic development of intercultural competence as an integral component of strategic internationalisation. By linking empirical analysis with institutional interventions implemented within the project, it contributes to the discussion on the qualitative dimension of internationalisation and offers in higher education.